Impact of FDI, environment and institutional quality on health outcomes, health expenditure and healthcare system efficiency - Yahaya, Adamu (2017)
From the time health has been identified as a key factor in human development, a lot of commitments have been made by the international community through Millennium Development Goals (MDGs) and Sustainable Development Goals (SDGs) programs to improve health outcomes especially in the developing countries. The estimated period for the MDGs has elapsed but the majority of the developing countries could not achieve their health outcomes targets despite the tremendous resources committed within the 15 years of the program. Although there is an improvement in the health outcomes but the inability to meet the 2015 MDG health targets coupled with the high number of mortalities, ever increasing health expenditure and health systems inefficiencies remain the world unsettled issues especially to the developing countries. Therefore this research aims at exploring the indirect impact of FDI on health outcomes through income, poverty and education as the socioeconomic conditioning variables. Using system GMM estimator, the study provides evidence in support of both modernization and dependency theories whereby the impact of the FDI on health outcomes was found to be nonlinear. The impact is not conditioned on the level of income alone but poverty and education were also found to be important and significant conditioning variables. The second objective was to explore the impact of environmental quality on health expenditure and the nonlinearity relationship tendency between the two variables. This is motivated by the ever increasing health expenditure and the failure of the existing literature to account for environmental quality even though the greenhouse gases have also been rapidly increasing over the years. The same GMM was used and the study established the relevance of the greenhouse gases on the health expenditure by providing evidence of inverted U-shaped relationship (non-linearity) between the two variables. The third objective of the thesis evaluates the technical efficiency of healthcare systems and its determinants particularly the relevance of institutional quality in developing countries. The nonparametric DEA results show that most healthcare systems in developing countries are technically inefficient and the Tobit model result indicates that institutional quality is a significant determinant of healthcare system efficiency. Therefore it is concluded based on these findings that healthcare system in developing countries wastes 36% of the healthcare inputs. Consequently, less healthcare inputs can potentially produce the given level of the health outcomes in the systems. Institutional capacity can positively enhance technical efficiency of the use of the healthcare inputs in the developing countries. As a matter of policy implication, the developing countries should enhance investment policies to realize the potentialities of the FDI for socioeconomic transformation particularly human development indicators like health. It is also of utmost importance for developed world to assist the developing countries to fast-track their institutions, environment management capacity for efficient healthcare system.